Long Noncoding RNA: Function and Mechanism on Differentiation of Mesenchymal Stem Cells and Embryonic Stem Cells - Zhu, Jian; Wang, Yitian; Yu, Wei; Xia, Kaishun; Huang, Yuluan; Wang, Junjie; Liu, Bing; Tao, Huimin; Liang, Chengzhen; Li, Fangcai (Current Stem Cell Research & Therapy, 2019)
Background: Long suspected as transcriptional noise, recently recognized, long non-coding RNAs (lncRNAs) are emerging as an indicator, biomarker and therapy target in the physiologic and pathologic process. Mesenchymal stem cells and embryonic stem cells are important source for normal and therapeutic tissue repair. However, the mechanism of stem cell differentiation is not completely understood. Research on lncRNAs may provide novel insights into the mechanism of differentiation process of the stem cell which is important for the application of stem cell therapy. The lncRNAs field is still very young, new insights into lncRNAs function are emerging to a greater understanding of biological processes. Objective: In this review, we summarize the recent researches studying lncRNAs and illustrate how they act in the differentiation of the mesenchymal stem cells and embryonic stem cells, and discuss some future directions in this field. Results: Numerous lncRNAs were differentially expressed during differentiation of mesenchymal stem cells and embryonic stem cells. LncRNAs were able to regulate the differentiation processes through epigenetic regulation, transcription regulation and post-transcription regulation. Conclusion: LncRNAs are involved in the differentiation process of mesenchymal stem cells and embryonic stem cells, and they could become promising indicator, biomarker and therapeutic targets in the physiologic and pathologic process. However, the mechanisms of the role of lncRNAs still require further investigation.
Keywords: therapeutic targets